Clinical history of HIV infection may be misleading in cytopathology - Pantanowitz*, Liron (Medknow Publications, 2010)
Human immunodeficiency virus (HIV)-infected patients are at an increased risk for developing opportunistic infections, reactive conditions and neoplasms. As a result, a broad range of conditions are frequently included in the differential diagnosis of HIV-related lesions. The clinical history of HIV infection may, however, be misleading in some cases. Illustrative cases are presented in which knowledge of a patient's HIV status proved to be misleading and increased the degree of complexity of the cytologic evaluation. Case 1 involved the fine needle aspiration (FNA) of a painful 3 cm unilateral neck mass in a 38-year-old female with generalized lymphadenopathy. Her aspirate revealed a spindle cell proliferation devoid of mycobacteria that was immunoreactive for S-100 and macrophage markers (KP-1, PGM1). Multiple noncontributory repeat procedures were performed until a final excision revealed a schwannoma. Case 2 was a CT-guided FNA of a positron emission tomography positive lung mass in a 53-year-old man. The acellular aspirate in this case contained structures resembling fungal spore forms that were negative for mucicarmine and GMS stains, as well as cryptococcal antigen immunocytochemistry. A Von Kossa stain confirmed that these pseudo-fungal structures were calcified debris. Follow up revealed multiple calcified lung and hilar node based granulomata. Case 3 involved the cytologic evaluation of pleural fluid from a 47-year-old man with Kaposi sarcoma and recurrent chylous pleural effusions. Large atypical cells identified in his effusion were concerning for primary effusion lymphoma. Subsequent pleural biopsy revealed extramedullary hematopoiesis, documenting these atypical cells as megakaryocytes. These cases demonstrate that knowledge of a patient's HIV status can be misleading in the evaluation of cytology specimens, with potential for misdiagnosis and/or multiple procedures. To avoid this pitfall in the setting of HIV infection, common entities unrelated to HIV infection and artifacts should always be included in the differential diagnosis.